Analisis Perilaku Keteraturan Mengkonsumsi Tablet Tambah Darah dengan Kejadian Anemia pada Ibu Hamil - Yusro Paridah; Rico Januar Sitorus; Rostika Flora; Nurlaili Nurlaili; Risnawati Tanjung (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to analyze the relationship between consuming blood-added tablets and anemia in pregnant women in the Kepahiang District. The research design used in this study was quantitative analytic with a cross-sectional design. The results showed that most or as many as 56 people (55.4%) had a positive attitude towards the incidence of anemia. As many as 61 people (60.4%) had irregularly consumed blood-added tablets. Almost entirely or as many as 82 people (81.2%) experienced anemia, regular consumption of blood-added pills with anemia showed that 61 respondents who did not regularly consume blood tablets in total or as many as 60 respondents (98.4%) experienced anemia. In conclusion, there is a relationship between consuming blood-added pills with the incidence of anemia in pregnant women. Keywords: Anemia, Pregnant Women, Blood Add Tablets